(untitled) (Conferencea, 2023)
The article analyzes the state of innovative management of industrial enterprises operating in the branches of the national economy of our country and evaluates its specific features. In particular, existing problems in the innovative management of industrial enterprises were identified, and scientific proposals and practical recommendations aimed at solving them were developed.